penalaran Filosofis terhadap Pernikahan Via Telepon: penalaran Filosofis terhadap Pernikahan Via Telepon - Patongai, Alny Avasyah R; Kurniati; Aulia Shaafirah (UIR Press, 2025)
Marriage law has a very important place in Islam, because marriage law directs the implementation of family life which is an important aspect of social life, according to a person's position which is respected above other creatures. Marriage law is one of the teachings of the Islamic religion that must be followed and implemented based on the commands of the Al-Quran and the Sunnah of the Prophet. As time goes by, various issues related to marriage begin to increase. One of the influences is changes in tradition or culture, as well as the rapid development of modern technological devices, such as communication tools.The purpose of this research is to understand the dynamics of telephone marriages and analyze telephone marriages. This research is a literature study (library research) using descriptive methods.The results of the research show that getting married by telephone is basically the same as holding a wedding ceremony in general, but the difference is that it is not done in the same place or far apart. This marriage can take place if the conditions are met and there are certain reasons behind the marriage by telephone, such as differences in countries that do not allow prenuptial agreements to be signed in person.